SOCIALISM AND NATIONALISM: A COMPARISON BETWEEN THE THOUGHT OF H.O.S. TJOKROAMINOTO AND ALIMIN PRAWIRODIRJO - Sarah Nuraini Siregar; Firman Noor; Lili Romli (Akademika : Jurnal Pemikiran Islam, 2022)
Oemar Said Tjokroaminoto and Alimin bin Prawirodirdjo were Indonesian founding fathers who played a salient role in the national movement and represented two influential groups and ideas of their time, Islamism, and communism. Due to their significant roles in the Indonesia independent movement and the broader Indonesian political thought, exploring their ideas is important. Hence, this article aims to analyze their thoughts on nationalism and socialism. By using a qualitative approach, this study traces two sources of data. First, references that contain the statements of these two figures and other scientific references. Second, confirming them based on analysis of two key informants' interviews. The study has demonstrated that Tjokroaminoto and Alimin's views on socialism and nationalism overlap in some regards and diverge in other aspects.